Estudio de mejora para la gestión de inventario y reducción de productos desechados - Rojas Arcos, Christian Fernando (2021)
The objective of this research work was to reduce the level of waste and raise the ERI in the LlevateloYa Company, seeking to achieve an economic benefit, making it possible to have a greater control of inventory and product non-conformity for an optimal organization and classification of its products. It began with the information gathering process carried out through visits to the company's warehouse, questionnaires and interviews with personnel. The information collected was processed and analyzed to obtain a synthesis of data and to be able to identify the problems that the company faces and then propose points for improvement. The first point that he began to deal with was the review of the demand forecast, it will give the company inventory levels, which means avoiding excess stock without compromising the level of service. For this, it was necessary to identify those products that were outside the control limits by sales category within the month, the Pareto 80-20 diagram was used, considering at least 100 products that represented 80% of monthly sales. The ABC classification gave us a total of 2089 processed products that register movement by sales, of which 487 products correspond to class “A”, 662 to class “B” and 940 to class “C”.